PENGARUH KOMPOSISI ARAH LAPISAN TERHADAP SIFAT PAPAN BAMBU KOMPOSIT - I.M. Sulastiningsih; Surdiding Ruhendi; Muh. Yusram Massijaya; Wayan Darmawan; Adi Santoso (Jurnal Penelitian Hasil Hutan, 2014)
The objective of this study was to determine the effect of layer orientation composition on the properties of bamboo composite lumber (BCL). Bamboo strips for BCL fabrication were prepared from mature culms (± 4 years old) of andong bamboo (Gigantochloa pseudoarundinacea (Steudel) Widjaja) collected from private gardens in West Java. The strips were pre-treated by soaking it in 7% boron solution for 2 hours. Five-layer BCLs were manufactured with 4 different compositions of layer orientation. The BCL was manufactured using water based polymer-isocyanate (WBPI) adhesive. The glue spread and cold pressing time applied were 250 g/m² and 45 minutes, respectively. Results showed that the average density, moisture content, thickness swelling, and width expansion of BCL were 0.79 g/cm³, 12.60%, 2.38%, and 1.13%, respectively. No delamination occurred in all samples using WBPI adhesive, which indicating high bonding quality. The average bonding strength (dry test) of BCL was 70.4 kg/cm². The physical and mechanical properties of BCL were significantly affected by layer orientation composition. The mechanical properties of BCL decreased as the number of cross-layer increased in the BCL structure. On the contrary, the present of cross-layer in BCL structure increased dimensional stability of the produced BCL.